2021
DOI: 10.3390/ijms22094339
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sarcopenic Obesity in Cancer and Cardiovascular Disease: A Synthesis of the Evidence on Pathophysiological Aspects and Clinical Implications

Abstract: Obesity is globally a serious public health concern and is associated with a high risk of cardiovascular disease (CVD) and various types of cancers. It is important to evaluate various types of obesity, such as visceral and sarcopenic obesity. The evidence on the associated risk of CVD, cancer and sarcopenic obesity, including pathophysiological aspects, occurrence, clinical implications and survival, needs further investigation. Sarcopenic obesity is a relatively new term. It is a clinical condition that prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 128 publications
(245 reference statements)
0
27
0
Order By: Relevance
“…Sarcopenic obesity (SO) is related to not only aging but also cardiovascular diseases (CVDs) and metabolic diseases such as insulin resistance (IR), type 2 diabetes (T2DM), and obesity ( 1 ). A recent review reported that more than one in 10 older adults face a health crisis due to SO ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenic obesity (SO) is related to not only aging but also cardiovascular diseases (CVDs) and metabolic diseases such as insulin resistance (IR), type 2 diabetes (T2DM), and obesity ( 1 ). A recent review reported that more than one in 10 older adults face a health crisis due to SO ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The British Regional Heart Study, conducted in older men of 60–79 years of age, although found a significant association between SO and cardiovascular mortality, failed to demonstrate an association between SO and coronary heart disease events. Ultimately, the association between SO and individual cardiovascular risk factors—atherogenic lipids profile with low high-density lipoprotein cholesterol (HDL-C) and high triglyceride levels, increased hs-CRP and IR acts together and increases the overall cardiovascular risk and mortality ( 196 ).…”
Section: Sarcopenic Obesity: a Separate And Different Entity?mentioning
confidence: 99%
“…At the same time, adipose tissue enhances the secretion of pro-inflammatory actin in muscle tissue. On the other hand, myocytokines (↓IL-15, ↓irisin, ↓IGF-1, ↑myostatin, impaired IL-6 secretion) may lead to muscle atrophy and dysfunction, they may play an endocrine role to aggravate fatty tissue inflammation and propagate a pro-inflammatory state between myocytes and adipocytes [ 5 , 49 - 52 ]. A summary of the possible mechanisms is shown in Figure 1 .…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
“…Further, the dietary pattern of elderly people, which is often characterized by insufficient protein intake combined with excess dietary calorie intake that is rich in saturated fatty acids, coupled with a sedentary lifestyle promotes the occurrence of sarcopenic obesity [ 11 ]. SO shares a common pathogenic mechanism with a variety of chronic diseases such as diabetes, cardiovascular disease, and cancer, among others [ 7 , 8 , 49 ]. SO can lead to a variety of pathophysiological changes, such as excessive secretion of pro-inflammatory cytokines by adipose tissue, changes in the expression of adipocytokines by adipocytes, and fat accumulation in muscle [ 6 , 12 ].…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation